Psychometric properties of the Persian version of the hospitalized older adults’ dignity scale for measuring dignity during acute hospitalization - Alireza Mirzaei; Mobina Jamshidinia; Marzieh Jahani Sayad Noveiri; Reza Imashi; Roghayeh Yaghoobi Saghezchi; Mohammad Javad Jafari; Reza Nemati-Vakilabad (PLoS ONE, 2025)
Background Providing dignified care is an essential aspect of high-quality nursing, and upholding patients’ dignity is emphasized in the professional standards for nurses. This research evaluated the reliability and validity of the Persian version of the Dignity of the Elderly in Acute Hospitalization Scale (HOADS-P) for assessing dignity during acute hospitalization. Methods The HOADS was translated into Persian using the forward-backward method. A panel of ten older adults and experts assessed face and content validity. Construct validity was established through Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) involving 400 hospitalized older adults aged 60 years and older. Results The EFA found that the HOADS-P exhibited five latent factors, explaining 63.15% of the overall variance. Also, these factors were confirmed by CFA (CMIN = 123.872, DF = 79, p < 0.001, CMIN/DF = 1.568, RMSEA = 0.042, GFI = 0.953, CFI = 0.987, NFI = 0.966, RFI = 0.954, and PCFI = 0.743). Additionally, the HOADS-P demonstrated strong reliability, as indicated by a Cronbach’s alpha coefficient (α) of 0.946. Conclusion The Persian version of the Dignity of the Elderly in Acute Hospitalization Scale (HOADS-P) is a valid and reliable tool for assessing dignity during acute hospitalization in Iranian health service centers.